Chinese Language Theory Textbook: Challenges and Solutions - Vladimir Kurdyumov (ARPHA Proceedings, 2021)
Proposed is a project (or principles) of a new version for the textbook of theoretical Chinese grammar based on the Predicative Concept of Language and continuous to the 2005-2006 edition. The book would be more systematic and will consider in more detail the non-equivalence of the language levels in Chinese and in Russian; the Topic-prominent typology of Chinese will be will be considered in more depth, as well as the variety of regional variants of Chinese; the impossibility of assimilating the Topic-prominent grammar to the same in the inflectional Subject-prominent languages will be systematically argued.